Epicurean simplicity - Mills, Stephanie (Island Press, 2002)
When an activity raises threats of harm to human health or the environment, precautionary measures should be taken even if some cause and effect relationships are not fully established scientifically. This idea, known as the "Precautionary Principle," is seen by environmentalists and public health experts as the key to protecting ecological and human health.